Fairness In The World Economy : Us Perspectives On International Trade Relations - Zampatti, Beviglia (USA : Edward Elgar, 2006)
In an international context, fairness is particularly important, since only a system which is perceived by its participants as fair can command acceptance and compliance.
Includes bibliographical references and index.
Keywords: Economics